2015
DOI: 10.5152/dir.2014.14329
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pineal cyst in patients with cerebral palsy

Abstract: ORIGINAL ARTICLE PURPOSE Pineal cysts are common incidental findings during magnetic resonance imaging (MRI) examinations. The etiology of pineal cyst development is still unclear. We aimed to determine whether there is an association between periventricular leukomalacia and pineal cyst prevalence. METHODSClinical and MRI data of 201 patients with periventricular leukomalacia (110 female, 91 male; mean age, 6 years; range, 2-18 years) and 687 control patients (355 female, 332 male; mean age, 6 years¸ range, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…One possible mechanism to account for PC development is mild brain hypoxia in the perinatal period [4]. Ozmen et al reported a higher prevalence of PCs in patients with cerebral palsy and periventricular leukomalacia [5]. Some studies suggest that pineal necrosis (apoplexy) may lead to the subsequent creation of a glial scar in the form of a cyst [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism to account for PC development is mild brain hypoxia in the perinatal period [4]. Ozmen et al reported a higher prevalence of PCs in patients with cerebral palsy and periventricular leukomalacia [5]. Some studies suggest that pineal necrosis (apoplexy) may lead to the subsequent creation of a glial scar in the form of a cyst [6,7].…”
Section: Introductionmentioning
confidence: 99%